2016
DOI: 10.1016/j.ahj.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Understanding physician-level barriers to the use of individualized risk estimates in percutaneous coronary intervention

Abstract: Background The foundation of precision medicine is the ability to tailor therapy based upon the expected risks and benefits of treatment for each individual patient. In a prior study, we implemented a software platform, ePRISM, to execute validated risk-stratification models for patients undergoing percutaneous coronary intervention and found substantial variability in the use of the personalized estimates to tailor care. A better understanding of physicians’ perspectives about the use of individualized risk-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… 23 A qualitative evaluation of physicians' perspectives on the tool found that physicians did not use ePRISM because they preferred to rely on their personal experience, felt their own decision-making was sound, and worried that the model would lead to patients not being offered a potentially beneficial therapy. 24 Similarly, we found providers often preferred to rely on their clinical judgment, particularly when they distrusted the calculator.…”
Section: Discussionmentioning
confidence: 70%
“… 23 A qualitative evaluation of physicians' perspectives on the tool found that physicians did not use ePRISM because they preferred to rely on their personal experience, felt their own decision-making was sound, and worried that the model would lead to patients not being offered a potentially beneficial therapy. 24 Similarly, we found providers often preferred to rely on their clinical judgment, particularly when they distrusted the calculator.…”
Section: Discussionmentioning
confidence: 70%
“…While physician engagement in SDM is essential for the process to work as intended, prior research has suggested that several physician-level barriers exist to the incorporation of personalized risk models into clinical care. 29 Such findings suggest that formal medical education regarding approaches to risk stratification, shared decision-making and cost effectiveness is needed, to promote evidence-based decision-making and improve the quality and cost-effectiveness of health care in the United States. To honor patients' preferences and for patients to participate in treatment decisions, a transformation in the process of PCI and stent selection is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our finding that stent concordance was 98% for patients who preferred to receive DES and only 53% for patients who preferred to receive BMS suggests that physicians are prone to use DES and may be reluctant to change their decisionmaking when patient preferences differ from their own. 29 This finding warrants further investigation, to better understand and overcome such physician biases, and to better engage physicians in SDM to deliver treatment that is preferred by patients.…”
Section: Future Researchmentioning
confidence: 96%
“…Recently, the precision medicine is defined as an evidence-based approach that uses innovative tools and biological and data science to customize disease prevention, detection, and treatment, and improve the effectiveness and quality of patient care 28 . The foundation of precision medicine is the ability to tailor therapy based upon the expected risks and benefits of treatment for each individual patient 28, 29, 30. It is in contrast to a “one-size-fits-all” approach, in which disease treatment and prevention strategies are developed for the average person, with less consideration for the differences between individuals.…”
mentioning
confidence: 99%